2011
DOI: 10.1371/journal.pcbi.1001054
|View full text |Cite
|
Sign up to set email alerts
|

Using Transcription Modules to Identify Expression Clusters Perturbed in Williams-Beuren Syndrome

Abstract: The genetic dissection of the phenotypes associated with Williams-Beuren Syndrome (WBS) is advancing thanks to the study of individuals carrying typical or atypical structural rearrangements, as well as in vitro and animal studies. However, little is known about the global dysregulations caused by the WBS deletion. We profiled the transcriptomes of skin fibroblasts from WBS patients and compared them to matched controls. We identified 868 differentially expressed genes that were significantly enriched in extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 73 publications
(60 reference statements)
0
38
0
Order By: Relevance
“…Abnormal expression of FBN1 and its interactors have been reported before in heart diseases (Mohamed et al, 2009) and in connective tissue diseases (Henrichsen et al, 2011), providing an idea of their importance in those systems.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Abnormal expression of FBN1 and its interactors have been reported before in heart diseases (Mohamed et al, 2009) and in connective tissue diseases (Henrichsen et al, 2011), providing an idea of their importance in those systems.…”
Section: Resultsmentioning
confidence: 78%
“…FBN1 network components are already found deregulated in other syndromes/diseases (Henrichsen et al, 2011; Mohamed et al, 2009) indicates their importance for understanding heart-related disorders and abnormalities.…”
Section: Introductionmentioning
confidence: 96%
“…Like ABHD11, ABHD14A may be involved in the pathophysiology of Williams-Beuren syndrome (WBS). In contrast to the deletion of ABHD11 in WBS, ABHD14A expression is higher in skin fibroblasts from WBS patients [85]. In addition, ABHD14A is also a candidate gene associated with autism spectrum disorder, a genetically complex disorder [86].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 868 identified differentially expressed genes, these authors found significant overrepresentation in major histocompatibility complex genes and gene products that localize to the postsynaptic membrane (39). This study went on to identify modules specific to the transcriptional profile of WS fibroblasts and compare them to other studies analyzing the transcriptional profile of control fibroblasts.…”
Section: Williams Syndromementioning
confidence: 99%